An Empirical Investigation of Portfolio Optimisation Using the Markowitz Model - Yixi Ni (Malikussaleh University, Aceh, Indonesia, 2025)
In finance, portfolio optimisation involves an essential concept that requires determining the ideal combination of assets to optimise returns by lowering the return risk. The concept of efficient portfolios, which aims to attain the maximum return for a given level of risk or the minimum risk for a given level of return, was initially suggested by Markowitz's model. Considering an emphasis on the Shanghai Stock Exchange (SSE), this research explores portfolio optimisation using Markowitz's Portfolio Theory about the Chinese stock market. The objective is to identify the optimal stock portfolio from a selection of various companies listed on the SSE for the 2020-2024 periods, balancing risk and expected return. A purposive sampling method is used to select various stocks based on their historical performance, with stocks screened through a two-level process: first by correlation coefficients, and by their coefficient of variation to assess risk-return trade-offs. Weekly return rates of selected stocks from the SSE over four years are used for the analysis. Using the mean-variance optimisation approach, the ideal weights for each stock in the portfolio are determined using the expected return effect. The results show that the optimized portfolio, consisting of various stocks (Industrial and Commercial Bank of China (ICBC), GD Power Development Co., Ltd, Beiqi Foton Motor Co., Ltd., Shanghai Automotive Industry Corporation (SAIC Motor), China Life Insurance Company (LIC)), performs more effectively with the return in trading days. The portfolio includes companies with diversified sectors, ensuring a balanced risk and return profile.